The Role of Work Ethic, Work Environment, Leadership Style and Training on Employee Performance of Fujipan Co., Ltd. in Saitama, Japan - Agung Kurniawan; Muhamad Al Faruq Abdullah (Greenation Research & Yayasan Global Resarch National, 2024)
Japan is one of the well known developed countries with culture ethos high work, where? many developing countries make Japan a country as role model in his business become a developed country. Study This carried out in companies operating in the field processing food named Fujipan. This company is one of the oldest companies more from 100 years and still operate until moment This. Research purposes is For describe role ethos work, style leadership, environment work and training to performance employee Fujipan in help development and progress company. Research methods used? is method qualitative with technique observations and interviews to worker Fujipan. Result of study This is ethos work, environment work, and training implemented at Fujipan have role positive in performance employee. But style leadership Still not enough give role positive to performance employee. In conclusion is in a way general Fujipan has succeed apply culture good and consistent work? in guard performance employee, who became factor supporter existence company until moment This. However need exists enhancement in style leadership implemented in place? Work.